Evaluation of Different Aquaculture Feed Ingredients in Indonesia Using Life Cycle Assessment - Patrik John Gustav Henriksson; Chadag Vishnumurthy Mohan; Michael John Phillips (Indonesian Life Cycle Assessment Network (ILCAN), 2017)
Indonesia’s aquaculture industry has grown by almost 25% annually over the last five years, an achievement enabled through the increased use of commercial aquaculture feeds, made from agricultural, capture fisheries and livestock resources. The reliance of aquaculture on capture fisheries has, however, attracted criticism, as has the land use consequences of imported Brazilian soybeans. Sourcing more sustainable resources has thus become part of maintaining a good environmental image and to secure long-term growth. In the present study we applied LCA to a number of feed ingredients used by the Indonesian aquaculture industry, including local fishmeal, rice and maize, as well as imported soybean, wheat and livestock byproduct meal (BPM). The impact categories global warming, acidification, eutrophication, land occupation and freshwater consumption were evaluated. Shrimp byproduct meal was generally associated with the largest emissions, followed by poultry byproduct meal. Wheat bran from Australia was the agricultural product with the largest acidification impacts, while rice bran had largest freshwater requirements. Overall, however, a shift is needed away from the overexploited local fish stocks towards alternative substitutes.